Attentional control predicts change in bias in response to attentional bias modification - Basanovic, J.; Notebaert, L.; Grafton, B.; Hirsch, C.; Clarke, Patrick (Elsevier, 2017)
© 2017 Elsevier Ltd Procedures that effectively modify attentional bias to negative information have been examined for their potential to be a source of therapeutic change in emotional vulnerability. However, the degree to which these procedures modify attentional bias is subject to individual differences. This generates the need to understand the mechanisms that influence attentional bias change across individuals. The present study investigated the association between individual differences in attentional control and individual differences in the magnitude of bias change evoked by an attentional bias modification procedure. The findings demonstrate that individual differences in two facets of attentional control, control of attentional inhibition and control of attentional selectivity, were positively associated with individual differences in the magnitude of attentional bias change. The present findings inform upon the cognitive mechanisms underpinning change in attentional bias, and identify a target cognitive process for research seeking to enhance the therapeutic effectiveness of attentional bias modification procedures.